Safety and Tolerability of Omalizumab: A Randomized Clinical Trial of Humanized Anti‐IgE Monoclonal Antibody in Systemic Lupus Erythematosus. Issue 7 (8th May 2019) - Hasni, Sarfaraz; Gupta, Sarthak; Davis, Michael; Poncio, Elaine; Temesgen‐Oyelakin, Yenealem; Joyal, Elizabeth; Fike, Alice; Manna, Zerai; Auh, Sungyoung; Shi, Yinghui; Chan, Diana; Carlucci, Philip; et al.
Abstract : Objective: Autoreactive IgE antibodies have been implicated in the pathogenesis of systemic lupus erythematosus (SLE). We hypothesize that omalizumab, a monoclonal antibody binding IgE, may improve SLE activity by reducing type I interferon (IFN) production by hampering plasmacytoid dendritic cells and basophil activation. This study was undertaken to assess the safety, tolerability, and clinical efficacy of omalizumab in mild to moderate SLE. Methods: Sixteen subjects with SLE and a Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI‐2K) score of ≥4 and elevated autoreactive IgE antibody levels were randomized to receive omalizumab or placebo (2:1) for 16 weeks, followed by 16 weeks of open‐label treatment and a 4‐week washout period. The SLEDAI‐2K score, British Isles Lupus Assessment Group index (BILAG 2004) score, and physician's global assessment of disease activity were recorded at each visit. The type I IFN–induced gene signature was determined using quantitative polymerase chain reaction. Results: Omalizumab was well tolerated with no allergic reactions, and mostly mild adverse events comparable to those experienced with placebo treatment. SLEDAI‐2K scores improved in the omalizumab group compared to the placebo group at week 16 ( P = 0.038), as well as during the open‐label phase in subjects initially receiving placebo ( P = 0.02). No worsening in BILAG scores or the physician's global assessment was detected. There was a trend toward a reduction in IFN gene signature in subjects treated with omalizumab ( P = 0.11), especially in subjects with a high baseline IFN signature ( P = 0.052). Conclusion: Our findings indicate that omalizumab is well tolerated in SLE and is associated with improvement in disease activity. Larger randomized clinical trials will be needed to assess the efficacy of omalizumab in patients with SLE.